Modelling of Thermal Power Plant for the Needs of Q-V Characteristic Control on HV Bus Bars - Pavlović, Jelena; Gajić, Tomislav; Dragosavac, Jasna; Janda, Žarko; Dobričić, Sava; Arnautović, Dušan (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
In this paper, a mathematical model of the thermal power plants TENT A and TENT B, developed for voltage and reactive power control simulation purposes, is presented. The model is developed using the Simulink/Matlab program platform. All important elements, such as synchronous generator, step-up transformer, turbine and governor, excitation system, automatic voltage regulator (ARN) and the network, connected to the power plant’s bus bars, are modelled with the complexity level required for studying the problems of interest. In the first part, a review of the hierarchical voltage control in the system is given, because the coordinated reactive power regulator (GRRS) has to be embedded in future processes of voltage control automatisation on higher levels and “smart” control in the power system. For the needs of studying the HV bus bars voltage control, as well as reactive power allocation within the power plant in manual and automatic control mode, a series of simulations was performed. For verification purposes, the simulation results are compared to the on-site measurements. An excellent match of simulated and recorded results is achieved.